2000
DOI: 10.1136/oem.57.8.563
|View full text |Cite
|
Sign up to set email alerts
|

Risk of mesothelioma from exposure to crocidolite asbestos: a 1995 update of a South African mortality study

Abstract: person-years, respectively. The mortality for lung cancer (29 deaths) was 287 (135-436) per 10 6 person-years, and that for other non-respiratory cancers (60 deaths) was 593 (442-745). Two cases of laryngeal and four of colon cancer were observed. All cancer mortality, mesothelioma, and lung cancer proportional cancer mortality ratios were increased. Conclusion-The mortality for mesothelioma in men was twice that in women, probably because men were more likely to have had both occupational and environmental ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…The average annual mortality rates for mesothelioma determined from two cohort studies in the region was 85 per million per year during 1977-83 and 178 per million per year during 1987-95. The latter rate is lower but in the same order as the rate of 277 per million person-years (95% CI 170-384) found for mesothelioma in the mortality study of the birth cohort in the South African crocidolite mining district of Prieska (Kielkowski et al, 2000). Age-standardised mesothelioma incidence has been reported for past residents of Wittenoom without occupational exposure to asbestos (Hansen et al, 1998).…”
Section: Non-occupational Mesothelioma In South Africamentioning
confidence: 88%
See 3 more Smart Citations
“…The average annual mortality rates for mesothelioma determined from two cohort studies in the region was 85 per million per year during 1977-83 and 178 per million per year during 1987-95. The latter rate is lower but in the same order as the rate of 277 per million person-years (95% CI 170-384) found for mesothelioma in the mortality study of the birth cohort in the South African crocidolite mining district of Prieska (Kielkowski et al, 2000). Age-standardised mesothelioma incidence has been reported for past residents of Wittenoom without occupational exposure to asbestos (Hansen et al, 1998).…”
Section: Non-occupational Mesothelioma In South Africamentioning
confidence: 88%
“…In a review of 504 cases from four of the above studies (White et al, 2008), the exposure was attributed to the environment in 23% in total. The 1973 Webster and1984 Solomons studies are probably the least reliable in terms of proportions of environmentally-induced cases; if these two are ignored the remaining studies are fairly consistent: in South African mining regions the proportion of environmental cases is in the order of 29% (Kielkowski et al, 2000;Mothemela, 2011) and between 16% and 19% for the country as a whole (Zwi et al, 1989;Rees et al, 1999a;Cochrane and Webster, 1978).…”
Section: Non-occupational Mesothelioma In South Africamentioning
confidence: 99%
See 2 more Smart Citations
“…In the Republic of South Africa several regions around asbestos mines have been heavily polluted and epidemiological studies have shown that regional MM mortality rates were twice as high in men as well as in women as compared with national mortality rates, whereby especially the high mortality among women was indicative for environmental exposure (Reid et al, 1990;Kielkowski et al, 2000;Braun and Kisting, 2006). Abratt et al (2005) have estimated that in South Africa approximately 26% of all MM cases can be attributed to environmental asbestos exposure.…”
Section: Introductionmentioning
confidence: 99%